THE REASONABILITY OF REDUCED TAX RATES ON FOODSTUFFS: AN ANALYSIS OF OPTIMAL TAXATION, TAX INCIDENCE AND TAX PASS-THROUGH - Turkia, Lauri (My University, 2024)
In this thesis, I study the reasonability of reduced tax rates particularly for foodstuffs. I investigate it from three angles, optimal taxation, tax incidence and pass-through. Reduced tax rates are common tools in tax systems. It is often said that they help the poor, but in theory they are not very effective distributional tools. Foodstuffs are taxed with reduced rates in many countries and thus offer an interesting area of research. Furthermore, the competition in retail market for foodstuffs is usually not described as perfect. Thus, I also investigate the connection between tax pass-through and competition. Taxes distort consumption and thus literature of optimal taxation mostly suggests uniform consumption taxation. Possible gains from different tax rates for different commodities lie in taxing products complement to leisure. Since there are few estimates of leisure complementarity of different goods, it is hard to use this logic to argue for reduced rates. In addition to optimal taxation, I review the literature on tax incidence, beginning with classic results for perfect competition. In perfect competition, generally the less elastic side bears the burden of tax. With imperfect competition, there are additional elements that define tax incidence. Market power and shape of demand can increase or decrease the tax burden. In the empirical part of this thesis, I analyze pass-through of VAT changes in foodstuffs in European Union between years 1996 and 2021. I find an asymmetry between tax increases and decreases. Increases are passed through to greater extent than decreases. At least for increases, it seems that pass-through increases when competition decreases. Due to the limited amount of tax decreases, I am not able to draw conclusions on the connection between competition and pass-through of decreases.
Keywords: optimal taxation, tax pass-through, tax incidence, retail competition